Antibacterial poly(ethylene oxide) electrospun nanofibers containing cinnamon essential oil/beta-cyclodextrin proteoliposomes. (15th December 2017) - Lin, Lin; Dai, Yajie; Cui, Haiying
Highlights: The cinnamon essential oil/β-cyclodextrin (CEO/β-CD) proteoliposomes were prepared. The proteoliposomes had high encapsulation efficiency of CEO. The controlled release of CEO in nanofibers was realized via bacterial protease. The nanofibers containing CEO/β-CD proteoliposomes showed high antibacterial activity. Abstract: A novel antibacterial packaging material was engineered by incorporating cinnamon essential oil/β-cyclodextrin (CEO/β-CD) proteoliposomes into poly(ethylene oxide) (PEO) nanofibers by electrospinning technique. Herein, PEO was a stabilizing polymer and used as electrospinning polymeric matrix for the fabrication of CEO/β-CD proteoliposomes nanofibers. The nanoliposomes were inlaid with protein are defined as proteoliposomes. Taking advantage of bacterial protease secreted from Bacillus cereus (B. cereus), the controlled release of CEO from proteoliposomes was achieved via proteolysis of protein in proteoliposomes. The CEO/β-CD inclusion complex was prepared by the aqueous solution method and characterized by Raman and FTIR spectroscopy. After the treatment of CEO/β-CD proteoliposomes nanofibers packaging, the satisfactory antibacterial efficiency against B. cereus on beef was realized without any impact on sensory quality of beef. This study demonstrated that the CEO/β-CD proteoliposomes nanofibers can significantly extend the shelf life of beef and have potential application in active food packaging.